1993
DOI: 10.1093/infdis/168.3.763
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Specific IgG Antibodies for Monitoring the Effect of Anti-Helicobacter pylori Chemotherapy

Abstract: A total of 104 patients with recurrent duodenal ulcer were treated with either ranitidine plus amoxicillin plus metronidazole or ranitidine plus placebo. To study the effect of the eradication of Helicobacter pylori on the systemic immune response in an IgG ELISA, sera were drawn from all patients before the onset of therapy and at 6, 16 +/- 2, 32 +/- 2, and 60 +/- 2 weeks after therapy. In patients with eradication of the organism, a significant (P < .001) reduction of the specific IgG titer occurred. This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 11 publications
3
33
1
1
Order By: Relevance
“…The results of the present study also show that these antibodies were detected in a high percentage of all groups studied, as has been reported in Asia. However, the data presented here differ from those previously reported in Asian countries, where antibodies to VacA and CagA proteins were detected with similar high rates in symptomatic and asymptomatic persons [20][21][22][23][24][25][26]. Thus, immunoblot studies conducted by Ogura et al [26] in Japan showed that antibody rates to a recombinant VacA protein were similarly high among patients with duodenal ulcer (95%), gastric ulcer (85%), chronic gastritis (95%) and …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the present study also show that these antibodies were detected in a high percentage of all groups studied, as has been reported in Asia. However, the data presented here differ from those previously reported in Asian countries, where antibodies to VacA and CagA proteins were detected with similar high rates in symptomatic and asymptomatic persons [20][21][22][23][24][25][26]. Thus, immunoblot studies conducted by Ogura et al [26] in Japan showed that antibody rates to a recombinant VacA protein were similarly high among patients with duodenal ulcer (95%), gastric ulcer (85%), chronic gastritis (95%) and …”
Section: Discussioncontrasting
confidence: 99%
“…Serological methods have been used to determine H. pylori colonisation in epidemiological studies [21,22] and to monitor the success of triple therapy [23,24]. Several reports from developed countries [10,11,15,21] have suggested that antibodies to CagA protein are present at significantly higher frequencies in peptic ulcer patients than in those with chronic gastritis or in healthy colonised individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, serology is encouraged in diagnosing such patients (5). Reports indicated that a 40-50% decrease in H. pylori antibody titers within 5-6 months following eradication continues, and titers reach normal values within 2 years (19,32,33). In our study the decline was statistically significant and further confirmed eradication of H. pylori.…”
Section: Discussionsupporting
confidence: 84%
“…In applying the different criteria to our patient population, it became apparent that the abilities of the systems to detect active H. pylori infection were quite varied. Since it is known that less than 2% of patients who harbor H. pylori fail to seroconvert (17,20,21,34,35,37), an optimally sensitive Western blotting system should be able to detect approximately 98% of active infections. The only interpretation system that approached this sensitivity was our currently used system (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the commercially available enzyme-linked immunosorbent assay (ELISA) systems are based on the detection of immunoglobulin G (IgG) antibodies against whole-cell preparations of H. pylori (14,16,17,23,24). Such preparations include antigens cross-reacting with other bacterial species, resulting in a specificity of these tests that rarely exceeds 90% (36,37,38).…”
mentioning
confidence: 99%